The effect on consumers of a sustainable supply chain in the domestic furnishings industry - xing, yilin (2020)
Sustainable development is a global issue. After entering the 21st century, human beings are more aware of the importance of sustainable development. The home furnishing industry will involve transnational and trans-regional supply chain issues. Therefore, for the home furnishing industry, supply chain management is essential, to achieve sustainable development of the supply chain is also important. As a vital link at the end of the supply chain, consumers' purchasing power directly affects the profitability of enterprises. Faced with the sustainable development problem of globalization, it is of reference significance to study the impact of sustainable development supply chain management on consumers' shopping choices by enterprises. As a global furniture company, IKEA was the first to implement sustainable supply chain management, which was divided into three aspects: resources and energy; life that occupy the home; human resources and community. Therefore, this study takes Ikea as an example to study the impact of IKEA's management methods on Chinese consumers' shopping choices. To fill in the gaps in this part of the research. The empirical research in this paper is to analyze the primary quantitative data. The data were collected through questionnaires in Beijing, China. The results gathered from the questionnaire were sorted out and visualised by EXCEL software. Statistical analysis software STATA was used to study the attitudes of Chinese consumers towards IKEA's sustainable supply chain through correlation analysis, regression analysis and variance analysis. It also analyses the different influences of consumers' income and consumers' attitudes towards IKEA in terms of resources, environment, people and community on purchasing intention. The sample size contains 152. Women accounted for 62.5%, while men accounted for 37.5 %. The conclusion of the study proves that consumers' income, IKEA's different practices in the three aspects of resources and energy, life that occupy the home, human resources and communities all have a positive impact on consumers' purchase intention.